Measuring fault tolerance in IoT mesh networks using Voronoi diagram. (March 2022) - Adhinugraha, Kiki; Rahayu, Wenny; Hara, Takahiro; Taniar, David
Abstract: In an IoT network, a gateway plays a pivotal role that enables it to connect to the cloud services or external networks. In a fog/edge infrastructure, multiple gateways work simultaneously to prevent bottleneck for both inbound and outbound traffic. While gateway failure is inevitable, some diversion strategies to minimize the impact of network outage are needed. In this paper, we propose a generalization model of order- k hops Voronoi diagram to provide precomputed k backup gateways and evaluate several gateway diversion strategies to redirect a router from multiple gateway failures to an alternate gateway with the closest hops. Our simulations show that device blackout during multiple gateway failure can be minimized by using at least 4 precomputed gateways. Furthermore, our model is able to identify the maximum x -chain failure that can be tolerated during multiple gateway failure.